DAMPAK KETIDAKSESUAIN ERGOMONI SARANA KURSI KAYU PADA KENYAMANAN PENDIDIK : FIELD STUDY AMM YOGYAKARTA - Fauzi, Syahrul; Isnaini, Rohmatun Lukluk; Dzunur'aini, Rosyidah; Fajrin, Nidaul (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic), 2023)
Abstract The incompatibility of the ergonomics of the wooden chair has an impact on the teacher's lack of comfort during the learning process. In addition, ergonomics incompatibility will have an impact on the health of educators in the long term. The purpose of this study was to analyze the impact of the ergonomics of wooden chairs on the comfort of educators. This study uses a qualitative-exploratory method in which the data obtained are in accordance with the phenomena that occur in the field (natural setting). This research model is a case study located in the TKA-TPA unit of AMM Kotagede Yogyakarta, data collection techniques are carried out by means of interviews, observation, and documentation. Sampling used purposive sampling consisting of directors as well as educators and education staff. The data will be analyzed by going through the stages of transcription, coding, grouping, comparing and contrasting. Data validity will be done by triangulation of sources and techniques. The results showed that 3 out of 8 educators stated that the wooden chairs used were not an obstacle during the learning process, this could be seen from the factor of their small body posture so that they could adjust to existing facilities. 5 other educators feel uncomfortable in their sitting position by using wooden chairs that adjust to the students because they have a high posture so that the sitting position is bent and the legs are always bent, this will have an impact on their health in the long term. The contribution given is that the TKA-TPA AMM unit provides 2 wooden chairs and 1 teacher's desk for the teaching staff. During private recitals, students are called forward one by one and sit in front of the teacher using a chair the same size as the teacher's chair.